Factors Affecting Zinc and Copper Metabolism During Development in The Piglet Model - Wang, Zheng Z. (My University, 1993)
This research investigated absorption, distribution and utilization of Zn and Cu in developing piglets as a model for human premature infants, specifically focusing on the impact of diet (amount and ratios of minerals), drugs (dexamethasone) and stage of development on mucosal cell membrane Zn and Cu transport and body Zn and Cu storage. In 32 and 52 h old piglets, velocity of Zn transport across intestinal brush border membranes (BBM) was higher than in 10 and 20 d old piglets but occurred via a nonsaturable mechanism. Cu transport across BBM was greater in the 20 d group than in 10 d, 32 h and 52 h groups and occurred mainly via a saturable mechanism in 32 h, 10 d and 20 d groups. Plasma Zn and Cu were significantly lower but tissue Zn, Cu and metallothionein (MT) contents were higher in the younger groups than the 10 and 20 d groups. Competition for transport between elements may also be important in infants since Cu transport across BBM was suppressed by Zn but enhanced by Fe at the ratios of Zn:Cu and Fe:Cu which are similar to those in premature infant formulas. Further studies indicated that Fe mainly increases Cu binding to BBM. High dietary Zn intake did not alter Zn transport across BBM but induced Zn accumulation in the intestinal mucosa and liver in piglets. These results are valuable in determining appropriate upper limits for Zn, Cu and Fe contents in infant formula. Exogenous dexamethasone (DEX) when used therapeutically to induce lung maturation in premature infants may compromise Zn and Cu status. Zn influx across BBM was significantly greater but Zn efflux was significantly lower in DEX treated compared to control piglets. The effect of DEX on Zn influx was abolished by dietary Zn supplement. Intestinal Cu uptake was also enhanced by DEX treatment. However, DEX-induced mucosal uptake of Zn and Cu did not appear to result in increased net Zn and Cu absorption since intestinal MT was induced by DEX. This study provides evidence that DEX treatment alters Zn and Cu metabolism in early life. Zn and Cu status should be carefully monitored in premature infants receiving long-term DEX therapy.
Keywords: Medical Sciences; Medical Sciences